Reductive Dehalogenation and Conversion of 2-Chlorophenol to 3-Chlorobenzoate in a Methanogenic Sediment Community: Implications for Predicting the Environmental Fate of Chlorinated Pollutants - Becker, Jennifer G. (American Society for Microbiology, 1999)
Biotransformation of 2-chlorophenol by a methanogenic sediment community resulted in the transient accumulation of phenol and benzoate. 3-Chlorobenzoate was a more persistent product of 2-chlorophenol metabolism. The anaerobic biotransformation of phenol to benzoate presumably occurred via para-carboxylation and dehydroxylation reactions, which may also explain the observed conversion of 2-chlorophenol to 3-chlorobenzoate.